Pengaruh FDR, PSR, Zakat Performance Ratio, dan Dana Pihak Ketiga Terhadap Market Share Dengan ROA Sebagai Variabel Mediasi - Sari, Indah; Aisyah, Esy Nur (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to determine the effect of Financing to Deposit Ratio (FDR), Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), and Third-Party Funds (DPK) on Market Share with Return On Assets (ROA) as a Mediation Variable. This study is quantitative. The object of this research is Islamic Commercial Banks in Indonesia which are registered with the Financial Services Authority (OJK) and Bank Indonesia (BI). The sample used the purposive sampling technique and produced 8 BUS in Indonesia. The data in this research is secondary data in an annual report from 2014 to 2020. The method used is path analysis using SPSS version 26 software for data analysis. The results showed that the FDR, PSR, ZPR, and DPK variables simultaneously impacted ROA. And FDR, PSR, ZPR, DPK, and ROA impact market share. Partially , ZPR PSR, and DPK impact ROA, then ZPR,DPK and ROA affect Market Share. At the same time, the FDR variables have no impact on ROA. Then FDR and PSR, do not influence market share. Furthermore, the results of the mediating role show that the ROA variable mediates the relationship between FDR, PSR ZPR, and DPK on Market Share.